2012
DOI: 10.4028/www.scientific.net/amm.263-266.448
|View full text |Cite
|
Sign up to set email alerts
|

Study on AC Stray Current Corrosion Law of Buried Steel Pipelines

Abstract: AC stray current can cause AC corrosion and destroy the safe operation of buried pipelines, which comes mainly from nearby high voltage transmission lines and AC electric railway. The research and evaluation lags far behind DC stray current at home and abroad, besides, the AC current density measuring procedures are complex. Through experimental study of different parameters on the impact of the AC current density established a mathematical model of damaged area, soil resistivity, pipe-to-soil potential and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Stray currents, originating from mass transit systems and overhead electricity pylons and substations, can result in severe corrosion of underground assets (Flounders and Danilyak, 1995;Wang et al, 2013). Zhu et al (2011) have suggested that soils with a higher resistivity can counteract the issue of stray currents by limiting the soils' current carrying capacity.…”
Section: Engineering Sustainabilitymentioning
confidence: 98%
“…Stray currents, originating from mass transit systems and overhead electricity pylons and substations, can result in severe corrosion of underground assets (Flounders and Danilyak, 1995;Wang et al, 2013). Zhu et al (2011) have suggested that soils with a higher resistivity can counteract the issue of stray currents by limiting the soils' current carrying capacity.…”
Section: Engineering Sustainabilitymentioning
confidence: 98%
“…Focusing on the analysis of the corrosion mechanism of stray current on buried steel pipes, domestic and foreign researchers have done a lot of investigations and studies on the influence of factors such as AC-DC stray current density, pipeline defect area, and external environment on the corrosion of buried steel pipes. In addition, in the study on the corrosion mechanism of AC stray current, Scholars have proposed five typical hypothesis models through theoretical analysis, experimental verification, field detection and other methods [6][7]. However, due to the fact that AC corrosion process is prone to interference by various factors and the process is relatively complex, the cause and process of AC corrosion are different and cannot be unified [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, AC voltage can interfere in the normal operation of cathodic protection system [9,[16][17][18][19][20][21], or cause polarity reversal in pipelines with the sacrificial anode, leading to the pipeline lack of effective protection. Therefore, it is very necessary to study the influence of AC stray current on the cathodic protection system.…”
Section: Introductionmentioning
confidence: 99%